Significance of Markers of Monocyte Activation (CD163 and sCD14) and Inflammation (IL‐6) in Patients Admitted for Alcohol Use Disorder Treatment. (3rd December 2019) - García‐Calvo, Xavier; Bolao, Ferran; Sanvisens, Arantza; Zuluaga, Paola; Tor, Jordi; Muga, Robert; Fuster, Daniel
Abstract : Background: Monocyte activation and inflammation are prominent features of alcohol‐related liver disease; however, they have not been thoroughly assessed in patients with alcohol use disorder (AUD) without overt liver disease. This study aimed to analyze associations among clinical and laboratory variables and markers of monocyte activation (CD163 and sCD14), and inflammation (interleukin [IL]‐6) among AUD patients. Methods: We analyzed the aforementioned associations in the highest quartile in 289 patients (77.5% male; median age, 50 years) consecutively admitted for alcohol detoxification in 2 tertiary hospitals in the Barcelona metropolitan area, Spain. Results: Median alcohol intake was 142 g/d; median glucose, albumin, creatinine, and bilirubin levels (mg/dl), 92, 40, 0.78, and 0.69, respectively; median AST, 41 U/l; median hemoglobin, median corpuscular volume, and platelet count, 14.1 g/dl, 94.8 fL, and 189 × 10 9 /l, respectively; median cholesterol, triglyceride, fibrinogen, and ferritin levels, 187 mg/dl, 109.3 mg/dl, 341 mg/dl, and 177 ng/ml, respectively. In addition, 36.7% patients had an erythrocyte sedimentation rate >20 mm, 32.5% had a C‐reactive protein (CRP) level of >5 mg/l, and 10.9% were hepatitis C virus (HCV)‐positive. Median CD163, sCD14, and IL‐6 levels were 759, 1.68 × 10 6, and 4.37 pg/ml, respectively. On logistic regression analyses, glucose, AST, bilirubin, hemoglobin levels, and HCV infection (adjusted odds ratio [aORs]: 1.01, 1.02, 3.04, and 9.73, respectively) were associated with CD163. Glucose, AST, triglyceride, and CRP >5 mg/l (aORs: 1.02, 1.01, 1.00, and 3.49, respectively) were associated with sCD14. Alcohol consumption upon admission, MCV, total cholesterol levels, and CRP >5 mg/l (aORs: 0.99, 1.05, 0.99, and 2.56, respectively) were associated with IL‐6. Conclusions: Monocyte activation and systemic inflammation are associated with higher glucose, liver enzyme, and lipid levels, HCV infections, and CRP of >5 mg/l, thus potentially identifying patients with AUD at high risk of midterm poor outcomes. Abstract : In patients admitted for alcohol use disorder treatment without overt end stage liver disease, higher plasmatic levels of markers of monocyte activation and systemic inflammation are associated with higher glucose, liver enzyme and lipid levels, as well as with HCV infection, and a C Reactive Protein level >5 mg/l.